Effect of confined longitudinal optical-phonons on cyclotron resonance absorption full width at half maximum in quantum wells. (January 2020) - Thu Phuong, Le Thi; Dinh, Le; Hien, Nguyen Dinh
Abstract: In this study, using the projection operator method, we investigated the influence of longitudinal optical (LO)-phonon confinement on the cyclotron resonance (CR) effect in quantum wells by calculating the expression for the absorption power. The full width at half maximum (FWHM) was obtained for the CR peaks using a computational method. The numerical results were determined for GaAs quantum wells based on three models of confined phonons delineated by Ridley, Fuchs–Kliewer, and Huang–Zhu, and for the bulk phonons. The CR absorption FWHM increased as the magnetic field and temperature increased, but decreased as the well width increased. These results are in good agreement with those obtained theoretically by Singh and Kobori et al. In addition, the CR absorption FWHM had a smaller value for the bulk phonons and it changed more slowly than that for the confined phonons. Furthermore, the CR absorption FWHM was largest for the Huang-Zhu model among the three models of confined phonons, and smallest for the Ridley model. These results are also in agreement with those obtained theoretically by Rudin et al. Weber et al., and Bhat et al. In addition, phonon confinement was determined as very important over the small range of the well width and it should be considered when investigating the CR absorption FWHM. Highlights: Effect of phonon confinement on cyclotron resonance (CR) in quantum wells. Full width at half maximum (FWHM) obtained for CR peaks. CR absorption FWHM increases with magnetic field and temperature for phonon models. CR absorption FWHM decreases as well width increases for phonon models. Phonon confinement important in well width range and affects CR absorption FWHM.